Spirobifluorene-cored wide bandgap non-fullerene small molecular acceptor with 3D structure for organic solar cells. (March 2019) - Tan, Hua; Long, Yi; Zhang, Jun; Zhu, Jianing; Yang, Jia; Yu, Junting; Zhu, Weiguo
Abstract: In this paper, a wide bandgap small molecule (SF(BR)4 ) based on spirobifluorene (SF) core, which is flanked with 2, 1, 3-benzothiadiazole and end-capped with 3-ethylrhodanine groups is synthesized and investigated as a non-fullerene acceptor in solution-processed organic solar cells (OSCs). The SF(BR)4 shows a wide optical bandgap of 2.10 eV and great advantages with respect to the low bandgap donor material poly[(5, 6-difluoro-2, 1, 3-benzothiadiazol-4, 7-diyl)-alt-(3, 3‴-di(2-octyldodecyl)2, 2′; 5′, 2″; 5″, 2‴-quaterthiophen-5, 5‴-diyl)] (PffBT4T-2OD), such as well energy-level matching and complementary absorption. Furthermore, the three dimensional (3D) molecular geometry of SF(BR)4 helps to suppress the strong intermolecular aggregation in PffBT4T-2OD:SF(BR)4 blend, leading to efficient non-fullerene OSCs. The resultant devices show a power conversion efficiency (PCE) of 6.15%. To our best knowledge, the PCE is among the highest reported to date for 3D non-fullerene acceptors except perylene diimides derivatives. Graphical abstract: Highlights: A 3D-structured small-molecule acceptor, SF(BR)4, was designed and synthesized. The SF(BR)4 exhibited a wide bandgap of 2.10 eV. The PffBT4T-2OD:SF(BR)4 -based OSCs achieved a high PCE of 6.15%.